2015
DOI: 10.1890/14-0802.1
|View full text |Cite
|
Sign up to set email alerts
|

Ocean acidification through the lens of ecological theory

Abstract: Abstract. Ocean acidification, chemical changes to the carbonate system of seawater, is emerging as a key environmental challenge accompanying global warming and other humaninduced perturbations. Considerable research seeks to define the scope and character of potential outcomes from this phenomenon, but a crucial impediment persists. Ecological theory, despite its power and utility, has been only peripherally applied to the problem. Here we sketch in broad strokes several areas where fundamental principles of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
204
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 245 publications
(208 citation statements)
references
References 130 publications
3
204
0
1
Order By: Relevance
“…The prevalence of complex trophic interactions in marine ecosystems, often involving multiple species and indirect effects, means that behavioural alterations caused by elevated CO 2 levels are likely to make future ecosystem structure and function more difficult to predict. Increasing evidence for behavioural effects of elevated CO 2 on species at different trophic levels [3][4][5][6][7][8]12,15,16,18,20,21], including interacting species as demonstrated here, suggests that trait-mediated indirect interactions could be important in predicting the effects of ocean acidification on marine communities and deserve further attention [19].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The prevalence of complex trophic interactions in marine ecosystems, often involving multiple species and indirect effects, means that behavioural alterations caused by elevated CO 2 levels are likely to make future ecosystem structure and function more difficult to predict. Increasing evidence for behavioural effects of elevated CO 2 on species at different trophic levels [3][4][5][6][7][8]12,15,16,18,20,21], including interacting species as demonstrated here, suggests that trait-mediated indirect interactions could be important in predicting the effects of ocean acidification on marine communities and deserve further attention [19].…”
Section: Discussionmentioning
confidence: 64%
“…13: 20160797 levels are likely to result in a greater energetic demand, so reductions in prey-capture rate may have energy budget consequences for these predators. A shift in the balance of energy intake versus expenditure would have a direct effect on individual performance and could potentially impact on optimal foraging strategies [19]. Our previous research showed that elevated CO 2 levels (961 matm) alter antipredator behaviours of the prey snail, the humpbacked conch [3], making it more vulnerable to predation.…”
Section: Discussionmentioning
confidence: 99%
“…As awareness of OA has grown over the recent decade and a half, increased research capacity has been directed toward improving our scientific understanding of the problem. There is a growing appreciation of the complex synergies, interactions and feedbacks that exist between ocean biogeochemistry and individual species/entire ecosystem response and resilience across multiple time-and spatial scales (e.g., Ries et al, 2009;Andersson et al, 2014;Breitburg et al, 2015;Gaylord et al, 2015). This includes the interaction and interplay between warming, deoxygenation and OA, and other environmental changes such as nutrient pollution (e.g., Anthony et al, 2008;Reid et al, 2009;Atewerbehan et al, 2013;Bijma et al, 2013;Bozec and Mumby, 2015;Malone et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Based on what we already know about potential biological and ecological effects, OAH in the CCMLE has the potential to alter critical processes, such as nutrient cycling and food-web interactions, that determine the dynamics, diversity, and biological productivity of coastal and marine ecosystems (Gaylord et al, 2015). However, relatively few projections yet exist concerning OAH effects on the ecology of the CCLME or its societal benefits, which include valuable commercial and recreational fisheries, recreational industries, and coastal wetlands and shoreline habitats.…”
Section: Effects On Ecosystemsmentioning
confidence: 99%